The Influence of Competence and Work Motivation on Employee Performance Through Job Satisfaction as an Intervening Variable at the Patumbak District Office - Fian Kristiani Buulolo; Boby Indra Prayoga; Ratna Sari Dewi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to determine and analyze the influence of competence and work motivation on employee performance, both directly and indirectly through job satisfaction as an intervening variable at the Patumbak Subdistrict Office. The research applies a quantitative approach using path analysis. The sample consisted of 25 employees of the Patumbak Subdistrict Office, with data collected through a questionnaire. The results show that partially, both competence and work motivation have a positive and significant effect on employee performance, as well as on job satisfaction. Furthermore, job satisfaction also has a significant positive effect on employee performance. The path analysis results show that the direct effect of competence on performance (0.742) is greater than its indirect effect through job satisfaction (0.473), while work motivation also has a larger direct effect (0.866) than its indirect effect via job satisfaction (0.555). These findings indicate that job satisfaction plays a role as a partial intervening variable. Therefore, efforts to improve employee performance at the Patumbak Subdistrict Office should focus on strengthening competence and work motivation directly, accompanied by creating a work environment that supports job satisfaction.